228k views
2 votes
Taylor graphs the system below on her graphing calculator and decides that f(x)=g(x) at x=0, x=1, and x=3. Provide Taylor some feedback that explains which part of her answer is incorrect and why it is incorrect.

Taylor graphs the system below on her graphing calculator and decides that f(x)=g-example-1

2 Answers

2 votes

Answer:


Explanation:

f(x)=2x+1 n g(x)=2x^2+1,


at x=0, f(0)=1=g(0)


x=1, f(1)=3=g(1)


in general a straight line like f(x) and a parabola like g(x) will intersect at most 2 times. in this case, at x=0 n 1.


x=3, f(3)=2(3)+1=7, g(3)=2(3)^2+1=19


f(x)<>g(x) at x=3


taylor's answer is correct for x=0 n x=1 but incorrect for x=3


User Franck Dernoncourt
by
5.0k points
5 votes

Answer:


Explanation:

Given the two functions, f(x)=2x+1 and g(x)=2x^2+1,

we can calculate that for x=0,

f(0)=2(0)+1=1

g(0)=2(0)^2+1=1

f(0)=g(0)

for x=1,

f(1)=2(1)+1=3

g(1)=2(1)^2+1=3

f(1)=g(1)

for x=3,

f(3)=2(3)+1=7

g(3)=2(3)^2+1=19

So f(x) and g(x) are different at x=3.


User Ziming Song
by
5.7k points